Construction and assessment of the quality of a care protocol for insulin use in hospitalized children and adolescents - Sarah Arrais de Lavor; Carla Cristina de Sordi; Vanessa de Araújo Lima Freire; Débora Lira Correia; Rhanna Emanuela Fontenele Lima de Carvalho; Fernanda Jorge Magalhães; Sherida Karanini Paz de Oliveira (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to develop and assess the quality of a care protocol for safe insulin use in hospitalized children and adolescents. Methods: a methodological study developed in three stages: scoping review, protocol development, and quality assessment. The scoping review followed the JBI recommendations, using the PRISMA-ScR checklist. The protocol was constructed according to the Guide for the Construction of Healthcare Protocols, and quality assessment was carried out byjudges using AGREE II. Results: the protocol achieved a quality rating of 94.4% in the scope and purpose domain; 90.4% in stakeholder involvement; 96.1% in rigor of development; 95.2% in clarity of presentation; 92.8% in applicability; 97.6% in editorial independence; and 92.8% for overall guideline assessment. Judges made suggestions, most of which were accepted. Final Considerations: the protocol was constructed and assessed as a quality instrument recommended for use by healthcare professionals in the context of insulin therapy in pediatrics.